Pengembangan Media Pembelajaran Berbasis Canva Untuk Meningkatkan Motivasi dan Hasil Belajar Siswa Pelajaran IPS di SMP Negeri 6 Abang - Suteja, I Kade; Kertih, I Wayan; Suastika, I Nengah (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2024)
The aims of this research are to: Describe the procedures for developing Canva-based learning media, (2) Find out the effectiveness of developing Canva-based learning media to increase the motivation and learning outcomes of class VIIIA students at SMP Negeri 6 Abang. This development research uses the ADDIE model. The data collection method used is a questionnaire method for data on the validity of material experts and media experts as well as teacher practicality data. The results of this research are 1) the development procedure used in developing Canva-based learning media is the ADDIE model (1) analysis stage, (2) design stage, (3) development stage, (4) development stage implementation, and (5) evaluation stage. 2) The animated video learning media product developed is classified as effective, seen from the results of the validity of the material and media, a CV value of 1 is obtained, then the animated video learning media product developed is classified as practical, in general the practicality value for the interest aspect is 24.8 which is categorized as very good , the value of the material presentation aspect is 24.4 which is categorized as very good, the value of the language aspect is 24.5 which is categorized as very good. In general, the average practicality score is 24.5 in the very practical category, thus this animated video learning media can be used in classroom learning, so that the results of the effectiveness of the learning media can be obtained through analysis of student motivation questionnaires before it is applied and after the animated video learning media is applied. the learning process has increased from a percentage of 60% to 90%, which really motivates students to learn. Next, looking at student learning outcomes using N-Gain formula analysis, we got a score of 0.71, which is categorized as very effective for use in learning, so that student learning outcomes increase.